Potensi Biogas Dengan Pretreatment Substrat Kulit Kopi Menggunakan Campuran Rumen Sapi - Adelia Salwa (Fakultas Teknik, 2023)
Biogas is an alternative energy source to reduce the use of fossil fuels. This research aims to explore the potential production of biogas using pretreatment of coffee husk substrate, both biologically with civet dung and chemically with NaOH solution, and compare it with the process without pretreatment. The fermentation process is carried out by adding rumen microorganisms to each digester with variations in substrate composition and fermentation time for 35 days, with sampling times at 7, 14, 21, 28, and 35 days. Biogas testing is performed by measuring the methane (CH4) content and total solids (TS) in the substrate. The results of the research show that pretreatment of coffee husk substrate has a significant impact on biogas (CH4) production. Biological pretreatment with civet dung produced the highest methane gas, reaching 42.3724% on the 28th day of fermentation with a mixture of 50% coffee husk + 25% rumen + 25% water, while the process without pretreatment produced the lowest methane gas, at 6.38433% on the 7th day of fermentation. The total solids results indicate an increase and decrease in total solids content in the reactor with various treatments. The highest total solids result was obtained with biological pretreatment at 40.15%. This research indicates that biological pretreatment of coffee husk substrate with civet dung can increase biogas production efficiency, which can be a potential solution to reduce dependence on fossil energy sources and sustainably manage coffee husk waste.Keywords: Biogas, Pretreatment, Coffee Peel, Civet Dung, Rumen Microorganisms, Production Efficiency, NaOH Solution.